The feasibility of low iodine dynamic CT angiography with test bolus for evaluation of lower extremity peripheral artery disease. (December 2021) - Inoue, Akitoshi; Vrtiska, Terri J; Lee, Yong S; Vasconcelos, Rogerio N; Weber, Nikkole M; Halaweish, Ahmed F; Duba, Irene; Williamson, Eric E; Leng, Shuai; McCollough, Cynthia H; Fletcher, Joel G
Objective: This study aims to determine if low iodine dynamic computed tomography angiography performed after a fixed delay or test bolus acquisition demonstrates high concordance with clinical computed tomography angiography (using a routine amount of iodinated contrast) to display lower extremity peripheral arterial disease. Methods: After informed consent, low iodine dynamic computed tomography angiography examination (using either a fixed delay or test bolus) using 50 ml of iodine contrast media was performed. A subsequent clinical computed tomography angiography using standard iodine dose (115 or 145 ml) served as the reference standard. A vascular radiologist reviewed dynamic and clinical computed tomography angiography images to categorize the lumen into "not opacified", "<50% stenosis", " 50 ̶70% stenosis", ">70% stenosis", and "occluded" for seven arterial segments in each lower extremity. Concordance between low iodine dynamic computed tomography angiography and the routine iodine reference standard was calculated. The clinical utility of 4D volume-rendered images was also evaluated. Results: Sixty-eight patients (average age 66.1 ± 12.3 years, male; female = 49: 19) were enrolled, with 34 patients each undergoing low iodine dynamic computed tomography angiography using fixed delay and test bolus techniques, respectively. One patient assigned to the test bolus group did not undergo low iodine computed tomography angiography due to unavailable delayed time. The fixed delay was 13 s, with test bolus acquisition resulting in a mean variable delay prior to image acquisition of 19.5 s (range; 8–32 s). Run-off to the ankle was observed using low iodine dynamic computed tomography angiography following fixed delay and test bolus acquisition in 76.4% (26/34) and 100% (33/33) of patients, respectively ( p  = 0.005). Considering extremities with run-off to the ankle and without severe artifact, the concordance rate between low iodine dynamic computed tomography angiography and the routine iodine reference standard was 86.8% (310/357) using fixed delay and 97.9% (425/434) using test bolus ( p  < 0.001). 4D volume-rendered images using fixed delay and test bolus demonstrated asymmetric flow in 57.7% (15/26) and 58.1% (18/31) ( p  = 0.978) of patients, and collateral blood flow in 11.5% (3/26) and 22.6% (7/31) of patients ( p  = 0.319), respectively. Conclusion: Low iodine dynamic computed tomography angiography with test bolus acquisition has a high concordance with routine peripheral computed tomography angiography performed with standard iodine dose, resulting in improved run-off to the ankle compared to dynamic computed tomography angiography performed after a fixed delay. This method is useful for minimizing iodine dose in patients at risk for contrast-induced nephropathy. 4D volume-rendered computed tomography angiography images provide useful dynamic information.